2016
DOI: 10.1139/cjps-2016-0216
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of wheat (Triticum aestivum L.) intercropped with rapeseed (Brassica napus L.)

Abstract: Recent advances in agronomy include better understanding of biodiversity in the ecosystem and mechanisms of interactions between crop species. Intercropping encompasses two or more crop species growing together. Enhanced biodiversity in intercropping systems can increase productivity, stability, resilience, and resource-use efficiency of the intercropped species compared with sole-cropping. Feasibility of different wheatrapeseed intercropping patterns were evaluated under three nitrogen fertilizer rates (0, 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Reasonable intercropping could increase crop growth and productivity (Cecilio et al, 2011), efficient use of the resources water, nitrogen and radiation (Lithourgidis et al, 2011), macronutrients (Kübler et al, 2010;Neugschwandtner and Kaul, 2016a;Salehi et al, 2018) and micronutrients (Neugschwandtner and Kaul, 2016b), yield quality (Klimek-Kopyra et al, 2017) and lower the damage caused by diseases and pests (Hauggaard-Nielsen et al, 2001). However, yield decreases in intercropping have also been reported (Ebrahimi et al, 2017). Functional groups or typical species used in intercropping include legumes (e.g., clover, fenugreek, vetch, beans and peas) and non-legumes (e.g., barley, buckwheat, rye, oat, wheat and flax) (Petropoulos, 2002;Hamzei and Seyyedi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Reasonable intercropping could increase crop growth and productivity (Cecilio et al, 2011), efficient use of the resources water, nitrogen and radiation (Lithourgidis et al, 2011), macronutrients (Kübler et al, 2010;Neugschwandtner and Kaul, 2016a;Salehi et al, 2018) and micronutrients (Neugschwandtner and Kaul, 2016b), yield quality (Klimek-Kopyra et al, 2017) and lower the damage caused by diseases and pests (Hauggaard-Nielsen et al, 2001). However, yield decreases in intercropping have also been reported (Ebrahimi et al, 2017). Functional groups or typical species used in intercropping include legumes (e.g., clover, fenugreek, vetch, beans and peas) and non-legumes (e.g., barley, buckwheat, rye, oat, wheat and flax) (Petropoulos, 2002;Hamzei and Seyyedi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Current research indicates that there are significant interactions between legumes and non-legume crops in intercropping, affecting above-ground biomass production, formation of yield components, plant height, and stem and leaf characteristics (Zajaç et al, 2013;Neugschwandtner and Kaul, 2014;Klimek-Kopyra et al, 2020) and the uptake and use efficiency of macro-and micronutrients (Neugschwandtner and Kaul, 2015Kaul, , 2016aKaul, , 2016bZajaç et al, 2018). Under Central European conditions, grain and biomass yield advantages have been shown for intercrops of naked oat/faba bean (Klimek-Kopyra et al, 2015b) and wheat/rapeseed (Ebrahimi et al, 2017). Klimek-Kopyra et al (2018b) also indicated a negative effect of intercropping on selected physiological parameters with a significant reduction in the green area index (GAI) and the normalized difference vegetation index (NDVI) values in pea/ linseed intercrops.…”
Section: Discussionmentioning
confidence: 99%
“…benfits results from inter crop should be highly linked with soil micrhohizal functionalities. Wheat rapeseed intercropping with 6 rows of wheat+ 2 rows rapeseed could be an option to enhance yield benefits and rapeseed production [8]. Intercropping of wheat with canola, [17] had significant effects on grain and relative yields of wheat and canola.…”
Section: Role Of Pulse Crop Intercropping On Yieldmentioning
confidence: 99%